Rejection of arrest of a ship based on the non-maritime nature of the claim (edict of the Commercial Court No 10 of Barcelona, 21st May 2021) - Orbegozo Miguel, Xabier (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
In this case, the Court analyses the possibility of granting the arrest of a ship for a debt produced by the lessee, not the ship-owner. The arrest is denied since the claim is not considered as a maritime claim that enables the arrest of ship under these circumstances.
Keywords: International Convention on Arrest of Ships 1999; Spanish “Ley de Navegación Marítima”; Maritime liens; Maritime Law